2019
DOI: 10.1108/hff-01-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle transportation of CuO-H2O nanofluid in a porous semi annulus due to Lorentz forces

Abstract: Purpose The purpose of this paper is to research on CuO-water nanofluid Non-Darcy flow because of magnetic field. Porous cavity has circular heat source and filled with nanofluid. Lattice Boltzmann Method (LBM) has been used to simulate this problem. Design/methodology/approach In this research, LBM has been applied as mesoscopic approach to simulate water-based nanofluid free convection. Koo–Kleinstreuer–Li model is used to consider Brownian motion impact on nanofluid properties. Impacts of Rayleigh number,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…It was found that the heat transfer rate per unit area decreases with the increase of magnetic field intensity. Sheikholeslami et al [121,122] found that the convection and the temperature gradient decrease with the magnetic field strength and Hartmann number. Alnaqi et al [123] explored the influence of magnetic fields on the natural convection heat transfer rate of nanoparticles.…”
Section: Negative Effectmentioning
confidence: 99%
“…It was found that the heat transfer rate per unit area decreases with the increase of magnetic field intensity. Sheikholeslami et al [121,122] found that the convection and the temperature gradient decrease with the magnetic field strength and Hartmann number. Alnaqi et al [123] explored the influence of magnetic fields on the natural convection heat transfer rate of nanoparticles.…”
Section: Negative Effectmentioning
confidence: 99%
“…Choi 5 initially interpreted the expression Nanofluid. Sheikholeslami 6 simply stated a nanofluid is just a liquid comprising tiny sized elements known as nanoparticles. In general, such nanoparticles are made of ceramic , metals , metal nitrides , Ferro particles , carbon in various forms (diamonds, graphite and carbon nanotubes) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Another investigation based on utilization of nano-materials in a baffled U-shaped enclosure was numerically simulated by Ma et al [ 24 ]. The impact of Lorentz force in porous annulus in presence of CuO-H 2 O nanofluid was investigated by Sheikholeslamiet al [ 25 ]. Bondarenko et al [ 26 ] reported thermal features of Al 2 O 3 /H 2 O nano-material in a cavity with a feature of heat-generating element.…”
Section: Introductionmentioning
confidence: 99%